Transcriptional profiling of Actinobacillus pleuropneumoniae under iron-restricted conditions - Deslandes, Vincent (BioMed Central, 2007)
BACKGROUND: To better understand effects of iron restriction on Actinobacillus pleuropneumoniae and to identify new potential vaccine targets, we conducted transcript profiling studies using a DNA microarray containing all 2025 ORFs of the genome of A. pleuropneumoniae serotype 5b strain L20. This is the first study involving the use of microarray technology to monitor the transcriptome of A. pleuropneumoniae grown under iron restriction. RESULTS: Upon comparing growth of this pathogen in iron-sufficient versus iron-depleted medium, 210 genes were identified as being differentially expressed. Some genes (92) were identified as being up-regulated; many have confirmed or putative roles in iron acquisition, such as the genes coding for two TonB energy-transducing proteins and the hemoglobin receptor HgbA. Transcript profiling also led to identification of some new iron acquisition systems of A. pleuropneumoniae. Genes coding for a possible Yfe system (yfeABCD), implicated in the acquisition of chelated iron, were detected, as well as genes coding for a putative enterobactin-type siderophore receptor system. ORFs for homologs of the HmbR system of Neisseria meningitidis involved in iron acquisition from hemoglobin were significantly up-regulated. Down-regulated genes included many that encode proteins containing Fe-S clusters or that use heme as a cofactor. Supplementation of the culture medium with exogenous iron re-established the expression level of these genes. CONCLUSION: We have used transcriptional profiling to generate a list of genes showing differential expression during iron restriction. This strategy enabled us to gain a better understanding of the metabolic changes occurring in response to this stress. Many new potential iron acquisition systems were identified, and further studies will have to be conducted to establish their role during iron restriction.